Actin cytoskeletal inhibitor 19,20-epoxycytochalasin Q sensitizes yeast cells lacking ERG6 through actin-targeting and secondarily through disruption of lipid homeostasis - Watchaputi, Kwanrutai; Somboon, Pichayada; Phromma-in, Nipatthra; Ratanakhanokchai, Khanok; Soontorngun, Nitnipa (Scientific reports, 2021)
Repetitive uses of antifungals result in a worldwide crisis of drug resistance; therefore, natural fungicides with minimal side-effects are currently sought after. This study aimed to investigate antifungal property of 19, 20-epoxycytochalasin Q (ECQ), derived from medicinal mushroom Xylaria sp. BCC 1067 of tropical forests. In a model yeast Saccharomyces cerevisiae , ECQ is more toxic in the erg6 ∆ strain, which has previously been shown to allow higher uptake of many hydrophilic toxins. We selected one pathway to study the effects of ECQ at very high levels on transcription: the ergosterol biosynthesis pathway, which is unlikely to be the primary target of ECQ. Ergosterol serves many functions that cholesterol does in human cells. ECQ’s transcriptional effects were correlated with altered sterol and triacylglycerol levels. In the ECQ-treated Δ erg6 strain, which presumably takes up far more ECQ than the wild-type strain, there was cell rupture. Increased actin aggregation and lipid droplets assembly were also found in the erg6 ∆ mutant. Thereby, ECQ is suggested to sensitize yeast cells lacking ERG6 through actin-targeting and consequently but not primarily led to disruption of lipid homeostasis. Investigation of cytochalasins may provide valuable insight with potential biopharmaceutical applications in treatments of fungal infection, cancer or metabolic disorder.